Antibacterial Activity of Diorganotin(IV) Complexes of Some Schiff-Bases Derivatives - J. Rashan, Luay; A. Aziz, Asma'a; D. Sulayman, Kuther; A.K. Al-Allaf, Talal; A. Al-Shama'a, Manal (Asian Journal of Chemistry, 2010)
The antibacterial activity of thirteen diorganotin(IV) complexesof the general formula R2SnCl2.L, where R = Me, Bu, Ph and L =Schiff-bases derived from substituted and non-substituted 2- or 3-aminopyridine and 2-hydroxy or 2-hydroxy-3-methoxy benzaldehyde.have been examined in vitro against eight species of bacteria.Some of the complexes obtained showed a remarkable activitytowards S. typhimurium, while others displayed a significant activityagainst P. aeruginosa, at concentrations ranging between0.1-10 μg /mL, when compared with that of the antibiotics used inthis study, amoxicillin and chloramphenicol and the control(DMSO), where no activity was obtained.